EFEKTIFITAS PROGRAM PRAKERJA DALAM MEWUJUDKAN KESEMPATAN KERJA DI KECAMATAN POLEWALI KABUPATEN POLEWALI MANDAR - Irsyad Dhahri; Nurharsya Khaer Hanafi; Muhammad Iqbal (Jurnal Tomalebbi, 2022)
Abstrack: This study aims to determine (1) the legal basis of the pre-employment program (2) to determine the effectiveness of the pre-employment program in Polewali District, Polewali Mandar Regency.Â This research is a qualitative descriptive study. The types and sources of data used in this study are primary data sources and secondary data sources. Data collection techniques include: observation, interviews, and documentation. The data obtained from the study were collected and processed by qualitative descriptive data analysis.Â The results of the study show that: (1) The legal aspects of the Pre-Employment Card program are regulated in Presidential Regulation No. 76 of 2020 concerning Amendments to Presidential Regulation No. 36 of 2020 concerning Development of Work Competencies through the Employment Card Program and Law No. 13 of 2003 concerning Employment ( 2). The effectiveness of the pre-employment program card in terms of its implementation has not been effective due to the lack of mastery of technology in registering most of the participants of the pre-employment program are parents. Supervision of the pre-employment program is still not clear at the district level who is responsible for carrying out the supervision due to the lack of coordination between the central and regional parties in coordinating the recipients of the pre-employment program.Â